Rapid label-free analysis of Opisthorchis viverrini eggs in fecal specimens using confocal Raman spectroscopy. - Oranat Chuchuen; Thani Thammaratana; Oranuch Sanpool; Rutchanee Rodpai; Wanchai Maleewong; Pewpan M Intapan (PLoS ONE)
Opisthorchis viverrini, a human liver fluke, is highly prevalent in Southeast Asia. Definitive diagnosis of infection is usually achieved parasitologically through the discovery of fluke eggs in feces. However, the eggs of O. viverrini are difficult to differentiate morphologically from those of other minute intestinal flukes in fecal samples, even for experienced technicians. The present study developed a label-free optical methodology for analysis of O. viverrini eggs using Raman spectroscopy. Raman features of O. viverrini eggs were reported that can be used as marker bands for the efficient analysis of O. viverrini eggs in fecal specimens. The methodology presented here allows for the rapid detection of O. viverrini egg infection and can be readily and practicably applied in any clinical setting, even those in which a trained parasitologist is not available.